PENGARUH PEMBERDAYAAN DALAM PENGEMBANGAN PARIWISATA BERBASIS MASYARAKAT TERHADAP KESEJAHTERAAN MASYARAKAT DESA WISATA PAKSEBALI, KABUPATEN KLUNGKUNG - Mahardika, Kadek Adi; Utama, Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 10 (2020): VOL 9 NO 10, OKTOBER 2020 (2152 - 2389), 2020)
Tourism Village is a rural area that is used as a tourist attraction by offering authenticity to the village atmosphere. Community-based tourism development is also called the Community Based Tourism or CBT approach. CBT is community-based tourism that focuses on ownership, management and community involvement in tourism development. The purpose of this study was to analyze the effect of community empowerment and CBT implementation on community welfare in the Tourism Village of Paksebali, Dawan District, Klungkung. The study population was all families in the Paksebali Tourism Village with a sample of 93 respondents. The analysis technique is used Structural Equation Modeling Partial Least Square (SEM-PLS). The results found that the variable of community empowerment had a positive and significant effect on the implementation of CBT and on the welfare of the community in Paksebali Tourism Village, and the implementation of CBT mediated the effect of community empowerment on community welfare in the Paksebali Tourism Village. The manager of the Paksebali Tourism Village should always involve the active role of the community in its development, so that community empowerment is to be carried out in order to achieve superior and independent communities.